Crimes of the Kremlin - Yushenkov, Sergei; Journeyman Pictures (United Kingdom : Journeyman Pictures, 2004)
This video discusses about the Russian outspoken reformist politician, Sergei Yushenkov that was murdered by a lone gunman in April 2003
Keywords: Yushenkov, Sergei; Political crimes and offences; Russia -- Politics and government